EKSISTENSI URF DALAM KOMPILASI HUKUM ISLAM - Musa Aripin (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2018)
Islam is a religion that regards the society tradition and convention as the source of Islamic jurisprudential law with improvements and certain limitations. So that, it is very important for moslemsto know and carry out with devotion one of the methods of UshlFiqh to analyze deeply urf in society life which grow along with the current development